2008
DOI: 10.1590/s0085-56262008000200002
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic study of the subtribe Dicrepidiina (Elateridae, Elaterinae, Ampedini)

Abstract: ABSTRACT. A phylogenetic study of the subtribe Dicrepidiina (Elateridae, Elaterinae, Ampedini). It is presented a cladistic analysis of the Dicrepidiina aiming to test the monophyletism of the subtribe and to establish the relationships among the genera. The subtribe is composed by 36 genera and all of them, except Asebis, Lamononia, Neopsephus, Semiotopsis and Spilomorphus were included in the analysis. Fifty two species, especially the type-species of each genus were studied: Achrestus flavocinctus (Physor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…1" of Johnson and Chaboo (2015). Casari (2008Casari ( , 2013 showed that the genus-level classification within Dicrepidiina requires further study. This new species can be associated with Candèze's (1859) Section II, which is characterized by antennomere 3 being shorter and narrower than antennomere 4, and differs from Section congeners by its small size, antennomeres 2 and 3 each smaller than antennomere 4, and opaque and bicolored dorsal integument.…”
Section: Dipropus Losamigos Johnson New Species (Figs 4 14)mentioning
confidence: 99%
“…1" of Johnson and Chaboo (2015). Casari (2008Casari ( , 2013 showed that the genus-level classification within Dicrepidiina requires further study. This new species can be associated with Candèze's (1859) Section II, which is characterized by antennomere 3 being shorter and narrower than antennomere 4, and differs from Section congeners by its small size, antennomeres 2 and 3 each smaller than antennomere 4, and opaque and bicolored dorsal integument.…”
Section: Dipropus Losamigos Johnson New Species (Figs 4 14)mentioning
confidence: 99%
“…Terminology follows Calder (1996) & Costa et al (2010), except for (followed works in parentheses): wing venation and apical sclerotizations (Kukalova-Peck & Lawrence, 2004;Muona, 1993), density of punctures (Douglas, 2003), pterotergites (Friedrich & Beutel, 2006) and mouthparts (Casari, 2008). The term "pedunculate anterior sac" is used here in the sense of Douglas (2011).…”
Section: Taxonomic Revisionmentioning
confidence: 99%
“…2U). The free margin of metacoxal plate (Casari, 2008) is the expanded part of metacoxal plate that overlaps part of the metatrochanter and metafemur (Fig. 12O).…”
Section: Taxonomic Revisionmentioning
confidence: 99%
See 1 more Smart Citation
“…nov. is recorded from Pará and Mato Grosso states (Brazil). D. ramicornis is widely distributed, with records from United States of America (Texas), Mexico (Chontales), Nicaragua, Antilles (Cuba, Guadelupe, Saint Domingue), Argentina (Chaco, Formosa) and Brazil (Palisot de Beauvois, 1805, Candèze, 1859, Chevrolat, 1867, Champion, 1894, Schenkling, 1925, Blackwelder, 1944, Bruch, 1911, Golbach, 1994, Casari, 2008. From Brazil it was recorded only from Minas Gerais, Rio de Janeiro, São Paulo and Santa Catarina states, but now it was studied material also from Amazonas, Pará, Rondônia, Mato Grosso, Mato Grosso do Sul, Ceará, Goiás, Bahia, Espírito Santo and Paraná.…”
mentioning
confidence: 99%